Stress induction and antimicrobial properties of a lipid transfer protein in germinating sunflower seeds - Gonorazky, Ana Gabriela (2005)
Nonspecific lipid transfer proteins (nsLTPs) belong to a large family of plant proteins whose function in vivo remains unknown. In this research, we studied a LTP previously isolated from sunflower seeds (Ha-AP10), which displays strong antimicrobial activity against a model fungus. The protein is present during at least the first 5 days of germination, and tissue printing experiments revealed the homogeneous distribution of the protein in the cotyledons. Here we report that Ha-AP10 exerts a weak inhibitory effect on the growth of Alternaria alternata, a fungus that naturally attacks sunflower seeds. These data put into question the contribution of Ha-AP10 as an antimicrobial protein of direct effect on pathogenic fungus, and rather suggest a function related to the mobilization of lipid reserves. We also show that the levels of Ha-AP10 in germinating seeds increase upon salt stress, fungal infection and ABA treatment, indicating that it somehow participates in the adaptative responses of germinating sunflower seeds.